Synthesis of large Stokes shift and narrow emission indole–triazole–carboxamide peptidomimetics via MCR-click strategy. Issue 22 (1st June 2016) - Pathoor, Rajeena; Bahulayan, D.
Graphical abstract: Highlights: An efficient build/pair strategy for indole carboxamide peptidomimetics. Click with MCR concept is efficiently employed. The final structures are obtained in a three step process. The molecules can be potential lead for stage 2 Human African Trypanosomiasis. The molecules are also useful for making fluorescent probes for imaging. Abstract: A series of indole peptidomimetics with potential for the future emergence as efficient therapeutic agents for stage 2 Human African Trypanosomiasis (HAT) is described. The peptidomimetics are constructed based on a build-pair concept using green chemistry models like multicomponent coupling strategy and click chemistry. The photophysical properties of the molecules are promising and point to the added possibilities of these molecules for the development of optical imaging agents.